2017
DOI: 10.1038/s41598-017-10659-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations and distributions in the human olfactory bulb in Parkinson’s disease

Abstract: In Parkinson’s disease (PD), the olfactory bulb is typically the first region in the body to accumulate alpha-synuclein aggregates. This pathology is linked to decreased olfactory ability, which becomes apparent before any motor symptoms occur, and may be due to a local metal imbalance. Metal concentrations were investigated in post-mortem olfactory bulbs and tracts from 17 human subjects. Iron (p < 0.05) and sodium (p < 0.01) concentrations were elevated in the PD olfactory bulb. Combining laser ablation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 103 publications
(103 reference statements)
0
27
0
Order By: Relevance
“…One of the most common non-motor symptoms that is present in more than 90% of those suffering with PD is the loss of olfaction (hyposmia or anosmia depending on severity) 6 . Prior to the changes seen in the substantia nigra, α-syn pathology is present throughout the OFB and tract and is especially abundant in each compartment of the AON 5,7,8 . The AON is the neural conduit between the OFB and the piriform cortex, entorhinal cortex, amygdala and hippocampal formations 9,10 .…”
mentioning
confidence: 99%
“…One of the most common non-motor symptoms that is present in more than 90% of those suffering with PD is the loss of olfaction (hyposmia or anosmia depending on severity) 6 . Prior to the changes seen in the substantia nigra, α-syn pathology is present throughout the OFB and tract and is especially abundant in each compartment of the AON 5,7,8 . The AON is the neural conduit between the OFB and the piriform cortex, entorhinal cortex, amygdala and hippocampal formations 9,10 .…”
mentioning
confidence: 99%
“…It (Wood, Bilclough, Bowron, & Walker, ) has been reported that depression was occurred in 10%–45% PD patients, this is consistent with the results that 20 (30.3%) patients with depression and anxiety in this study. Olfactory function became apparent before any motors symptoms, which may be caused by local metal imbalance (Gardner et al., ). But may be due to the less number of cases in this study, the percentage of olfactory dysfunction in the study was 5 (7.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, motor symptoms of Parkinson were focused on, while it has been rarely mentioned, but these non-motor symptoms can seriously affect the life quality of patients with PD (Gardner et al, 2017;Mu et al, 2017;Muzerengi, Contrafatto, & Chaudhuri, 2007). All PD patients basically had different degrees of sleep disorders, most of them occurred at the early stages (Chaudhuri, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Free Ca 2+ concentrations in rat olfactory neurons reach ≈2 μ M during nerve stimulation [ 30 ]. Likewise, pools of Cu 2+ are released in and around olfactory neurons during signaling, reaching concentrations as high as 10 μ M in the synapse [ 31 34 ]. Further, despite high Cu 2+ concentrations, the olfactory bulb in rats does not have elevated expression of the typical copper chaperone metallothionein [ 35 ].…”
Section: Discussionmentioning
confidence: 99%